A Novel, Highly Sensitive ALK Antibody 1A4 Facilitates Effective Screening for ALK Rearrangements in Lung Adenocarcinomas by Standard Immunohistochemistry. Issue 4 (April 2015) - Gruber, Kim; Kohlhäufl, Martin; Friedel, Godehard; Ott, German; Kalla, Claudia
Abstract : Introduction: Successful treatment of lung cancer patients with crizotinib depends on the accurate diagnosis of anaplastic lymphoma receptor tyrosine kinase (ALK) gene rearrangements. The approved fluorescence in-situ hybridization test is complex and difficult to use in daily diagnostic practice. Immunohistochemical assays—rapid and perfectly adapted for routine pathology practice—have been proposed as alternatives. We evaluated the novel high affinity ALK 1A4 antibody for routine diagnostics in formalin fixed, paraffin-embedded tumor specimens. Methods: Detection of ALK protein expression was investigated by comparing the new 1A4 antibody and the established D5F3 antibody/Ventana system in 218 lung cancer specimens with known ALK status preanalyzed by quantitative reverse transcription-polymerase chain reaction and fluorescence in-situ hybridization (20 ALK -positive cases, 198 ALK -negative cases). Results: The accuracy of both immunohistochemical assays for the detection of ALK rearrangements was high. Using a conventional staining procedure without signal enhancement, the 1A4 antibody assay identified all 20 ALK -rearranged tumors (100% sensitivity) and correctly characterized 196 of 198 negative cases (99.1% specificity). The D5F3/Ventana assay detected 19 ALK -rearranged tumors and typed 217 of 218 tumors correctly (95% sensitivity, 99.5 % specificity). Conclusions: The novel 1A4 antibody represents a promising candidate for screening lung tumors for the presence of ALK rearrangements.